THE INFLUENCE OF GREEN ACCOUNTING AND FINANCIAL PERFORMANCE ON THE PROFITABILITY OF REAL ESTATE AND PROPERTY COMPANIES - Hadiyanto, Kevin; Icha Fajriana (Fakultas Ekonomi Universitas IBA Palembang, 2025)
This research aims to analyze the influence of green accounting, capital structure and financial performance on the profitability of real estate and property companies listed on the Indonesia Stock Exchange in 2022-2023. The research method uses a quantitative approach with secondary data in the form of company financial reports. Data analysis was carried out using multiple linear regression to determine the relationship and contribution of independent variables to profitability. The research used purposive sampling research techniques, with multiple linear data analysis. Apart from that, this research also identified a phenomenon of the Green Accounting variable, and Capital Structure has no influence on the financial performance variable (Financial Performance). However, unlike the Profitability level, this research has an influence on the financial performance variable (Financial Performance). Keywords: Green Accounting, Capital Structure, Profitability, Financial Performance